The Effect of Using Simulation-Based Learning on Nursing Performances of Early Postpartum Hemorrhage in Nursing Students - Kornkarn Pansuwan; Sirikanok Klankhajhon (Faculty of Nursing Universitas Padjadjaran, 2021)
Background: Early posypartum haemorrhage (PPH) is a crucial problem in maternal and newborn care. The simulation-based learning has an important role to improve knowledge, practical skills, and attitude in realistic case-based scenarios. Purpose: This study aims to examine the effect on using simulated scenario in the simulation laboratory on nursing performance of early postpartum hemorrhage of nursing students. Methods: The quasi-experimental research, one group pretest-posttest design was used to study with the nursing students from the Faculty of Nursing, Naresuan University in Academic Year 2019 during the period of December 1, 2019 to January 31, 2020. The subjects of thirty nursing students were selected by purposive sampling. The instruments were the the ability in nursing of early postpartum hemorrhage through the questionnaires which consists of the performance test and satisfaction before and after the early PPH simulation program. The content of scenario consists of the definition, etiology, risk factors, signa and symptoms, treatment, holistic nursing care, and continuous care. The data were analysed as the descriptive: numbers, percentages, frequency, mean and standard deviation. The paired t-test was used to compare the outcome between pre-test and post-test. Results: The data were analysed by t-test. The results illustrated that the students who learned through simulated scenario on performance in nursing care of women with early postpartum hemorrhage had, after learning, higher performance in nursing care of women with early postpartum hemorrhage than that before learning at the .01 level of significance. The students were satisfied learning by using the simulation program in the high level (x̄ = 4.26, S.D. = 0.54). Conclusion: The simulation-based learning improves the core competencies and performances of nursing students for management women with early postpartum hemorrhage as knowledge, potential clinical care skills, and attitude. It will be useful to implement for nursing care women regarding early postpartum hemorrhage in the real situations.